Characterization of colostrum from dams of BLV endemic dairy herds - Gutierrez, Gerónimo; Lomonaco, Marina; Alvarez, Irene; Fernandez, Fernando; Trono, Karina Gabriela (Elsevier, 2018)
Bovine Leukemia Virus (BLV) is endemic in Argentina, where the individual prevalence is higher than 80% in dairy farms. The aim of this work was to find preliminary evidence to know if the high level of infection of the dam would implicate a higher challenge to her own offspring. We collected 65 sets of samples consisting of dam's blood and colostrum from two heavily infected dairy farms, and investigated the correlation between the dam's blood proviral load and the presence of provirus in colostrum. We also described the dual antibody/provirus profile in the colostrum. Provirus was detected in 69.23% of the colostrum samples, mostly from dams with a high proviral load, 36/45 (80%). Colostrum proviral load was significantly higher in dams with high blood proviral load (p < 0.0001). Provirus was detected in colostrum samples all along the antibody distribution, even in those with a low amount of antibodies. These results show that even when high blood proviral load dams offer higher levels of infected cells to their offspring through colostrum they also offer higher levels of protection of antibodies. On the contrary, low blood proviral load dams also offer infected cells but a poor content of antibodies, suggesting that these animals could play an important role in the epidemiological cycle of transmission.